THE IMPLEMENTATION OF GRAPHIC ORGANIZER STRATEGY IN IMPROVING STUDENTS’ WRITING SKILLS ( A Classroom Action Research at the First Grade of Vocational High School of 2 Cilaku Cianjur) - Revi Reshifa (Universitas Suryakancana, 2020)
Writing skills is the ability to create something in a written form. This study was conducted to investigate the implementation of Graphic Organizer strategy to improve students’ writing skills. The subject of this research was the first-grade Graphic Design of Vocational High School of 2 Cilaku Cianjur, which involves 25 students. The implementation of Graphic Organizer strategy is an excellent teaching strategy for teaching students’ writing skill and building their critical thinking and also students’ creativity in writing. This study aims to investigate the process of Graphic Organizer Strategy in improving students’ writing skills, and students’ perception toward implementation Graphic Organizer Strategy. The method that used in this research was Classroom Action Research (CAR) method to identify and solve the problem on the students’ writing skills. The technique for data analyzing will be used cycle design from ( Strickland, 1987) in (Khasinah, 2013). The data were taken from observation, questionnaire, and test. The research was conducted in one class with 25 samples. It was applied in two cycles. Each cycle consists of six steps of action research (identified problem, plan research, collect data, analyze and interpret data, reflection, and share or take action). The research findings show that (1) the process of writing text in writing skill lesson using Graphic Organizer Strategy was interesting for students. (2) the results of the writing project in X Design Graphic class in writing skill using Graphic Organizer Strategy was improving. In the pre-cycle the average of the score was 64 or 20%, then in cycle I students’ score average was 74 or 48%, and for the last cycle, cycle II the average of students’ score was 82 or 76%. In cycle II, all students’ score was above the minimum achievement criteria that were 75. These result showed that students’ scores have achieved the achievement cycle. based on the results, it could be identified that using Graphic Organizer as the strategy in teaching writing could improve students’ writing skill. Key Words: Writing Skills, Graphic Organizer Strategy, Classroom Action Research (CAR)